2022
DOI: 10.1016/j.ultsonch.2022.105929
|View full text |Cite
|
Sign up to set email alerts
|

Insights into ultrasound-promoted degradation of naphthenic acid compounds in oil sands process affected water. Part I: Accelerated H-abstraction and decarboxylation of aromatic and alicyclic compounds

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…These modifications presented in Part 1 of this study were confirmed by the Fukui calculations and an additional NEB-TS calculation of benzoic acid to phenol by OH radical attacks yielded 3hBA as a transition state [5] . The Fukui coefficients of 3-hydroxybenzoic acid suggested 3, 4-dihydroxybenzoic acid as the product rather than the suggested 2, 3-dihydroxybenzoic acid.…”
Section: Dft and Fukui Indices For Reactive Sites Determinationsupporting
confidence: 73%
See 4 more Smart Citations
“…These modifications presented in Part 1 of this study were confirmed by the Fukui calculations and an additional NEB-TS calculation of benzoic acid to phenol by OH radical attacks yielded 3hBA as a transition state [5] . The Fukui coefficients of 3-hydroxybenzoic acid suggested 3, 4-dihydroxybenzoic acid as the product rather than the suggested 2, 3-dihydroxybenzoic acid.…”
Section: Dft and Fukui Indices For Reactive Sites Determinationsupporting
confidence: 73%
“…A reaction shift towards OH • radicals may be enhanced by the introduction of ozone or similar oxidants into the process. It was reported and confirmed [5] that during sonication, model organic acids such as benzoic acid, due to their volatile and hydrophobic nature, diffuse to the cavitation bubble and decompose by pyrolysis and/or OH • degradation by a range of steps as shown in Fig. 1 .…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations